A Four-Item Questionnaire to Measure Problematic Social Media Use: The Social Media Disorder Test - Wartberg, Lutz; Spindler, Carolin; Berber, Sophia; Potzel, Katrin; Kammerl, Rudolf (Behavioral Sciences, 2023)
While the use of video games and social media is an enjoyable recreational activity for most users, a minority develop problematic patterns of use. In the ICD-11, for the first time, there is a category of “disorders due to addictive behaviors” (including gaming disorder). The scientific literature also suggests a potential for the problematic use of social media. Economic screening tools for this are still needed. A very economical questionnaire to record gaming disorder is the ICD-11-based Gaming Disorder Test (GDT). The purpose of the present survey was to investigate the psychometric properties of an adapted questionnaire (Social Media Disorder Test, SMDT) to assess problematic social media use (PSMU). Therefore, 443 youths (mean age: 20.11 years) were examined with the SMDT and other measures regarding PSMU, self-control, and psychopathology. A confirmatory factor analysis (CFA) and reliability and correlation analyses were conducted. For the SMDT, we observed very good fit indices in the CFA, suggesting a one-factor structure; the reliability coefficient was 0.90, and we found the first indications for criterion validity. If the results can be confirmed, the SMDT, with its four questions, would be a very economical instrument to measure PSMU based on the ICD-11 criteria for behavioral addictions.
CRIS-Team Scopus Importer:2023-12-29
Keywords: assessment; gaming disorder; ICD-11; Internet addiction; psychometric properties; questionnaire; screening; SMDT; social media addiction; validation